PENGEMBANGAN SKEMA PATEN PADA SISTEM INFORMASI HAK KEKAYAAN INTELEKTUAL LPPM UNIVERSITAS DHYANA PURA - I Made Dwi Ardiada; Putu Wida Gunawan; Gerson Feoh (Jurnal informasi dan komputer, 2022)
According to the Directorate General of Intellectual Property of the Ministry of Law and Human Rights, a patent is defined as the exclusive right of the inventor to create or provide his work to be made in the field of art for a certain period of time. At Dhyana Pura University, one of the units, namely LPPM, has several activities which include the management of Intellectual Property Rights (IPR). On April 22, 2021, Dhyana Pura University received the Strengthening of Intellectual Property Rights Center of the Ministry of Research and Technology / National Research and Innovation Agency in 2021. Meanwhile, the Information System for the Management of Intellectual Property Rights (IPR) at LPPM only covers Copyright Applications. In addition, a digitalized patent filing facility is also needed at the University to support patent applications which are still minimal. In addition, the Incentive Revenue related to the Intellectual Property Rights Center also cannot cover the development of internal systems at the university. Therefore, it is necessary to develop a patent scheme for the IPR management system at the Dhyana Pura University LPPM which can display reports related to patent applications and can be accessed anywhere and anytime. With the development of a patent scheme on the system, it can provide convenience, speed and accuracy in Data processing so that it is expected to bring progress in the service of application and management of patent rights at LPPM Dhyana Pura University.